2015
DOI: 10.1109/tcsvt.2014.2363753
|View full text |Cite
|
Sign up to set email alerts
|

Fast HEVC Encoding Decisions Using Data Mining

Abstract:  Abstract-The High Efficiency Video Coding (HEVC) standard provides improved compression ratio in comparison to its predecessors at the cost of large increases in the encoding computational complexity. An important share of this increase is due to the new flexible partitioning structures, namely the Coding Trees, the Prediction Units and the Residual Quadtrees, with the best configurations decided through an exhaustive RateDistortion Optimization (RDO) process. In this article we propose a set of procedures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(73 citation statements)
references
References 26 publications
0
73
0
Order By: Relevance
“…Correa et al [19] Early CU termination using the offline trained decision trees and threshold values.…”
Section: B Related Workmentioning
confidence: 99%
“…Correa et al [19] Early CU termination using the offline trained decision trees and threshold values.…”
Section: B Related Workmentioning
confidence: 99%
“…A set of procedures for partition structure determination is designed in Ref. [18] to early terminate exhaustive RDO process using data mining techniques. An early terminating fast intermode decision algorithm, namely hierarchical intermode decision (HIMD), is presented in Ref.…”
Section: The Related Previous Workmentioning
confidence: 99%
“…Support vector machines have been used in [18]. More recently, a decision tree based method has been proposed to reduce the complexity of the HEVC encoder [19] . Although it is reported that the complexity of the HEVC encoder is reduced by the aforementioned techniques, the reduction is still limited.…”
Section: A Fast Transcoding Techniquesmentioning
confidence: 99%
“…However, the significant performance improvement of our proposed meth- ods implies that the proposed methods are notably efficient in reducing the complexity of an HEVC transcoder. Since each reference work yields different values of BDBR and time saving, we obtain the ratio between BDBR and time saving (B/T) [19]. This parameter shows the amount of BDBR loss per time saving.…”
Section: Performance Comparison With the State-of-the-artmentioning
confidence: 99%